Predicting Student Achievement in Ohio: The Role of Expenditure Distribution - Barbara M. De Luca; Steven A. Hinshaw (Educational Considerations, 2013)
In the spring of 2005, political columnist George Will coined the phrase the “65 percent solution” in his Washington Post column in reference to an Arizona referendum that would have required at least 65% of every school district’s operational budget be spent on classroom instruction.
Keywords: school district; expenditures; predicting; student; achievement; Ohio; variables; analysis; research; regression